2021
DOI: 10.1177/0969733021989180
|View full text |Cite|
|
Sign up to set email alerts
|

Ethical challenges and nursing recruitment during COVID-19

Abstract: The United Nations Global Compact for Migration 1 touted optimism for a more secure international migration of persons which would strengthen the development of health systems in low-and middleincome countries. The menacing COVID-19 pandemic caused dramatic setbacks in exertions to make migration safer also for health professionals. Advanced countries that heavily relied on international nursing mobility have witnessed a huge reduction in nursing flows during the pandemic. However, they will probably continue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…17 Before the pandemic, the World Health Organization reported a global nursing shortage of approximately 5.9 million nurses, indicating that a general shortage of nurses will contribute to a shortage of nursing leaders. 18,19 The COVID-19 pandemic has had a profound effect on nurse leaders as well as clinical nurses. 20 A cross-sectional study in Australia identified that 75% of nurse leaders had high levels of stress and anxiety related to the pandemic, and 41% of those surveyed had identified an intent to leave the workforce.…”
Section: An Integrative Reviewmentioning
confidence: 99%
“…17 Before the pandemic, the World Health Organization reported a global nursing shortage of approximately 5.9 million nurses, indicating that a general shortage of nurses will contribute to a shortage of nursing leaders. 18,19 The COVID-19 pandemic has had a profound effect on nurse leaders as well as clinical nurses. 20 A cross-sectional study in Australia identified that 75% of nurse leaders had high levels of stress and anxiety related to the pandemic, and 41% of those surveyed had identified an intent to leave the workforce.…”
Section: An Integrative Reviewmentioning
confidence: 99%
“…Pengalaman merupakan guru yang baik yang menjadi sumber pengetahuan dan juga merupakan suatu cara untuk memperoleh kebenaran pengetahuan. Pengalaman adalah peristiwa yang benar-benar pernah dialami (Notoatmodjo, 2014) Analisis data menggunakan pendekatan yang didasarkan pada teori (Creswell, 2014) (Stievano, Bakhshi, Shaffer, & Hamilton, 2021). Oleh karena itu, rumah sakit-rumah sakit berupaya memenuhi kebutuhan pelayanan dengan cara merekrut relawan, bahkan tidak hanya relawan medis tetapi relawan nonmedis (Fathimah & Nulhaqim, 2020).…”
Section: Pengalaman Perawatunclassified
“…There have been long‐standing criticisms in relation to nurses' recruitment from developing countries, which are blamed for skills and ‘brain drain’ (Kingma, 2006 ) and accused of being a legacy of British imperialism (Spiliopoulos & Timmons, 2022 ). In response, international and national ethical codes of practice for recruiting foreign nurses designed to balance the demand of labour, choices of professionals and the needs of developing countries were established: nurse migration was conceived of as a temporary professional experience which could benefit developing countries in the long‐term (Stievano et al, 2021 ). Although blamed for exploitative practices such as high fees and intrusive controls over migrant lives, labour market intermediaries were able to maintain their function globally as gatekeepers (Calenda & Bellini, 2021 ).…”
Section: Trajectories Of Nurse Migration To the Ukmentioning
confidence: 99%